Suitable coordinates for quantum dynamics: applications using the multiconfiguration time-dependent Hartree (MCTDH) algorithm - Joubert-Doriol, Loïc; Schröder, Markus; Vendrell, Oriol; Meyer, Hans-Dieter (Computational and theoretical chemistry, 2012)
We discuss the role of the coordinates for the convergence of quantum dynamical simulations involving motions of large amplitude. We put special emphasis on the MCTDH algorithm and discuss several illustrative examples that are parametrized by polyspherical coordinates. Finally, new sets of curvilinear coordinates for malonaldehyde and benzopyran are proposed.